Effects of dark boson mediated feeble interaction between dark matter (DM) and quark matter on f-mode oscillation of DM admixed quark stars - O. P. Jyothilakshmi; Lakshmi J. Naik; Debashree Sen; Atanu Guha; V. Sreekanth (European Physical Journal C: Particles and Fields)
Abstract We investigate the behavior of the prominent non-radial fundamental f-mode oscillations of dark matter (DM) admixed strange quark stars (DMSQSs), by adopting an equation of state (EoS) developed in Ref. Sen and Guha (Mon Not R Astron Soc 517:518, 2022. https://doi.org/10.1093/mnras/stac2675 ), which considers the possible presence of feebly interacting DM in strange quark stars (SQSs) for the first time. Within the model, feeble interaction between fermionic DM $$χ $$ χ and strange quark matter (SQM) is invoked via a vector new physics mediator $$ξ $$ ξ with coupling strength $$y_{ξ }$$ y ξ . The pure SQM is described by the vector MIT Bag model. By varying different EoS parameters, the structural properties viz. the mass, radius and tidal deformability ( $$Λ $$ Λ ) of the DMSQSs are studied with respect to various astrophysical constraints. We study in detail the f-mode spectra within the Cowling approximation by obtaining the frequencies as a function of mass, compactness and $$Λ $$ Λ of the star. To the best of our knowledge, this study represents the first analysis of non-radial f-mode oscillations of DMSQSs. Our investigation indicates that the presence of DM and its interaction with SQM has great impact on the f-modes. We show that the f-mode frequencies are larger for DMSQSs, which are largely populated with massive DM fermions, compared to the SQSs. Further, we obtain a linear empirical relation between the f-modes and the average density of the star. We also find that the mass-scaled angular frequency varies universally with compactness and $$\ln {Λ }$$ ln Λ for DMSQSs. Further, our studies indicate that the inclusion of DM in compact stars reduces the deviation of f-mode frequency from general relativistic to Cowling approximation.